Esophageal POEM: the new standard of care - Jawaid, Salmaan; Draganov, Peter V.; Yang, Dennis (Translational Gastroenterology and Hepatology, 2020)
Since its introduction into clinical practice nearly a decade ago, per-oral endoscopic myotomy (POEM) has now become an accepted minimally invasive approach for the treatment of achalasia with excellent short- and mid-term clinical outcomes in both treatment naïve and those who have failed prior therapy. POEM is comparable to laparoscopic Heller myotomy (LHM) in terms of efficacy and safety, with less procedural pain and faster recovery time. Recent data also reveals that POEM may be more effective and durable than pneumatic dilation (PD) for the treatment of achalasia, with similar safety profile. Preliminary data on POEM for spastic esophageal disorders (SED) is promising yet scarce. Post-POEM gastroesophageal reflux disease (GERD) is common but asymptomatic in most patients, further highlighting the need for ongoing research in this field and the importance of long-term surveillance of these patients.